Minority Report from the Committee on Rules and Order of Business (1968)
This Minority Report from the Committee on Rules and Order of Business proposes reforms to the delegate selection process for the 1972 Democratic National Convention. It calls for language in the convention's official call requiring state parties to ensure that delegates are chosen through processes allowing full and timely participation by all Democratic voters. Specifically, it demands the elimination of the unit rule at any stage of delegate selection and urges that delegates be selected through primaries, conventions, or committee procedures open to public participation within the convention year. The report emphasizes transparency and democratic inclusion in the selection process. A partial list of signatories from numerous states is included, reflecting broad support for these proposed reforms.